2007
DOI: 10.1007/s10461-007-9244-5
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Risk Behavior Among Persons With HIV in Medical Care

Abstract: We surveyed randomly selected patients in the largest HIV clinic in Seattle, WA in 2005 and 2006. A total of 397 patients completed usable surveys. Twenty-seven percent of men who have sex with men (MSM) and 22% of women or heterosexual men reported having non-concordant unprotected anal or vaginal intercourse in the preceding year. Compared to 2005, more MSM in 2006 reported meeting a sex partner via the Internet (15% vs. 33%), and fewer met partners in bathhouses (23% vs. 13%). Twenty-four percent of MSM rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…We surveyed almost 50% of the HIV-infected population in Croatia, however, and had a low refusal rate and wide inclusion criteria, which allowed us to generalize our findings to the entire HIV-infected population of about 400 persons under medical care in Croatia. Our findings were similar to behavioral data reported from recent studies in other settings (Golden et al 2007;Morin et al 2007), which showed that MSM were more likely to report risky sexual behavior than were MSW or women. Such studies have led to the development of national behavioral surveillance systems for HIV/ AIDS patients (Malitz and Eldred 2007).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We surveyed almost 50% of the HIV-infected population in Croatia, however, and had a low refusal rate and wide inclusion criteria, which allowed us to generalize our findings to the entire HIV-infected population of about 400 persons under medical care in Croatia. Our findings were similar to behavioral data reported from recent studies in other settings (Golden et al 2007;Morin et al 2007), which showed that MSM were more likely to report risky sexual behavior than were MSW or women. Such studies have led to the development of national behavioral surveillance systems for HIV/ AIDS patients (Malitz and Eldred 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Heterosexual patients of both sexes were more likely than MSM to expose their main partners to HIV and to report no casual non-concordant, unprotected sex in that period, a finding not reported in similar studies (Golden et al 2007;Morin et al 2007). There also was evidence of sero-sorting among MSW and women with casual partners.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…For illicit drugs, club drugs and 'sex-associated' substances (e.g. erectile dysfunction medication and amyl nitrite), we also found a significant relationship between drug consumption and sexual risk behaviour, concordant with previous findings in HIV-positive MSM samples [31,34,35]. As in previous studies [37,42,43], substance use in the direct context of sexual activity significantly increased sexual risk behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…Rates of the virus are alarmingly high among Black and Latina women, who accounted for 24% of US women and 82% of AIDS diagnoses in 2005 (CDC 2008). Although many women living with HIV/AIDS (WLH/A) practice safe sex, many also have risky sex, with roughly one-third having reported unprotected sex with their male partners (Aidala et al 2006;Golden et al 2007;Wilson et al 2004). Prevention programs for WLH/A can play an integral role in helping women adopt safer and healthier sex lives to protect their partners from acquiring HIV; protect themselves from acquiring sexually transmitted infections (STIs) or other strains of HIV/AIDS; and obtain emotional support as they cope with difficult intimacy or sexual concerns (Collins et al 2000;Kalichman 2004).…”
Section: Introductionmentioning
confidence: 99%